Socio-demographic Factors and Household Expenditure on Food Consumption in Ondo State, Nigeria - Olorunfemi, S.; Fatukasi, A. A.; Adeleye, O. K. (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Household expenditure on food consumption has become an issue of great concern in Nigeria today. This is so because an increasing percentage of the household in Nigeria was feeding less and therefore become more food insecure which made households suffer serious ailments arising from an acute deficiency in their diets. This study examined the effect of socioeconomic factors on household expenditure on food consumption in Nigeria. Data were gotten through the administration of questionnaires to 2500 household heads in three senatorial districts in Ondo State. The study adopted multistage sample techniques; we analyzed information extracted from the questionnaire using both descriptive and regression techniques. The result indicated that major source of income exerts a significant negative (t=-3.76, p<0.05) effect on household consumption expenditure in Ondo State, Nigeria, a positive relationship between household size and consumption expenditure (t=5,38, p<0.05), and a positive impact between education qualification and household expenditure for consumption (t-3.26,p<0.05). However, gender, age, marital status, and respondents’ senatorial districts did not get a significant effect on households’ consumption expenditure of food. The study recommended that government should try to pay workers’ salaries as at when due to discourage reduction in food consumption expenditure of the people